2019
DOI: 10.1016/j.ejvs.2018.08.041
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Sigmoidoscopy to Detect Colonic Ischaemia After Ruptured Abdominal Aortic Aneurysm Repair

Abstract: WHAT THIS PAPER ADDS This study determined the value of sigmoidoscopy to detect colonic ischaemia (CI) after repair of ruptured abdominal aortic aneurysm (RAAA). It demonstrates that sigmoidoscopy is mainly valuable in patients with a moderate clinical suspicion of CI. The probability of identifying a patient with transmural ischaemia increases from approximately 22% to 73% when moderate to severe CI is detected at sigmoidoscopy. Moreover, sigmoidoscopy is effective in ruling out the presence of CI. Objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Understanding the perioperative risk factors, early recognition of ischemia, and knowledge of the differences in intervention required for mucosal and transmural ischemia are critical to enhance patient outcome. 44,45 Similar advantages have been noted in the critical care of postoperative head and neck surgery patients, 46 pancreaticoduodenectomy patients, 47 and vascular surgery patients, 48 where understanding of anatomy, postoperative physiology, and postoperative complications provide optimal patient outcomes. In a single center study, admission of patients with necrotizing soft tissue infections to an ACS service was associated with a significant reduction in time to surgical source control compared with those admitted to a non-ACS service, 49 often because of more rapid, accurate diagnosis on the ACS service.…”
Section: Early Recognition Of Surgical Emergencies and Source Controlmentioning
confidence: 67%
See 1 more Smart Citation
“…Understanding the perioperative risk factors, early recognition of ischemia, and knowledge of the differences in intervention required for mucosal and transmural ischemia are critical to enhance patient outcome. 44,45 Similar advantages have been noted in the critical care of postoperative head and neck surgery patients, 46 pancreaticoduodenectomy patients, 47 and vascular surgery patients, 48 where understanding of anatomy, postoperative physiology, and postoperative complications provide optimal patient outcomes. In a single center study, admission of patients with necrotizing soft tissue infections to an ACS service was associated with a significant reduction in time to surgical source control compared with those admitted to a non-ACS service, 49 often because of more rapid, accurate diagnosis on the ACS service.…”
Section: Early Recognition Of Surgical Emergencies and Source Controlmentioning
confidence: 67%
“…For example, postoperative ischemic colitis following abdominal aortic aneurysm repair is a rare but lethal condition associated with a fourfold higher risk of adjusted in-hospital mortality. Understanding the perioperative risk factors, early recognition of ischemia, and knowledge of the differences in intervention required for mucosal and transmural ischemia are critical to enhance patient outcome 44,45 . Similar advantages have been noted in the critical care of postoperative head and neck surgery patients, 46 pancreaticoduodenectomy patients, 47 and vascular surgery patients, 48 where understanding of anatomy, postoperative physiology, and postoperative complications provide optimal patient outcomes.…”
Section: Early Recognition Of Surgical Emergencies and Source Controlmentioning
confidence: 90%
“…In a post hoc sub-analysis from the DREAM study data by Jalalzedah, 13% (n = 46) of cases underwent selective sigmoidoscopy evaluation among rAAA patients. 22 They reported a 73% PPV for moderate-to-severe colonic ischemia predicting transmural IC. The negative predictive value was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…As contrast, rates from studies that utilized selective endoscopy report an incidence of IC between 5 to 18% for EVAR, and 8 to 22% for open. 11,[15][16][17][18][19][20][21][22] These studies include the randomized control trials comparing EVAR and OSR, the AJAX, 15 and ECAR 16 trials. Our rates of IC derived from routine endoscopy yielded a higher number of diagnoses compared to studies that employed selective endoscopy, and this suggests that protocols involving selective endoscopy are likely failing to capture cases of IC.…”
Section: Incidencementioning
confidence: 99%
“…Most publications addressing risk factors for developing CI after AAA surgery have shown that repair of RAAA, in contrast to elective surgery, is an important determining factor [ 7 , 8 , 9 , 10 ]. Although many studies reported on risk factors for developing CI after aortic surgery, only a few reported on those after RAAA [ 9 , 10 , 11 ]. Additionally, many reports about CI focus on patients’ demographic, comorbidities, and operative factors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%